The problems surrounding health economic benefits: Who is in charge? - Vidal Coronado, Raúl Martín (2020)
This research paper addresses the problems surrounding economic health benefits, specifically, the economic benefit corresponding to temporary incapacity for work. For this purpose, the national regulation and the scope of the contributory regime of the social security in health will be analyzed, since this is the one that concentrates the largest number of insured -workers- and is responsible for the coverage of economic benefits for the latter.